2018
DOI: 10.29024/aogh.2375
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Intra-Uterine Device Users in Mirebalais, Haiti: A Mixed Methods Study

Abstract: Introduction:IUDs are safe, effective, and used worldwide to prevent unintended pregnancy. However, uptake in Haiti is low. There are limited data on IUD choice and experience in low resource settings; anecdotal reports from providers in Haiti have suggested that Haitian women are unlikely to choose to use or be satisfied with the IUD. The objective of this study is to explore the perceptions of a cohort of IUD users in Mirebalais, Haiti.Methods:In June and July 2015, an IRB-approved mixed methods study of wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Alignment between a method's duration of use and women's preferences facilitated the adoption and continued use of all methods except the female condom, which is a single-use, on demand method (Shapiro 2016;Machado et al 2013;Shapiro et al 2014;Somesh Kumar et al 2014;Das et al 2015;Minnis et al 2018;Shapley-Quinn et al 2019;Sheriar et al 2014;Van Der Straten et al 2018;Callahan et al 2019;Van Der Westhuizen and Hanekom 2016;Ndegwa et al 2014;Jairaj and Dayyala 2016;Eva et al 2018;Kakaire et al 2016;FHI360 and Family Health Options Kenya 2016, 360;FHI 360, SFH Nigeria, and PSI 2020b;USAID 2019;PSI et al 2019;Population Council 2016c;FHI 360 2012;Routes2Results et al 2019b;Danna et al 2019;FHI 360 2017;Van Der Straten et al 2010;Todd et al 2012;Bryant et al 2015;Gutin et al 2011;Ho and Wheeler 2018;Hubacher et al 2013;Da Costa et al 2019;Priyanka, Kaushik, and Paras 2015). For example, many studies found that women appreciated the long-acting nature of copper and hormonal IUDs because they saw this duration as convenient and low maintenance (Nanda et al 2018;Gottert et al 2015;Huber-Krum et al 2019;Mukamuyango et al 2020;Azmat et al 2012;Boller et al 2018;…”
Section: mentioning
confidence: 99%
See 4 more Smart Citations
“…Alignment between a method's duration of use and women's preferences facilitated the adoption and continued use of all methods except the female condom, which is a single-use, on demand method (Shapiro 2016;Machado et al 2013;Shapiro et al 2014;Somesh Kumar et al 2014;Das et al 2015;Minnis et al 2018;Shapley-Quinn et al 2019;Sheriar et al 2014;Van Der Straten et al 2018;Callahan et al 2019;Van Der Westhuizen and Hanekom 2016;Ndegwa et al 2014;Jairaj and Dayyala 2016;Eva et al 2018;Kakaire et al 2016;FHI360 and Family Health Options Kenya 2016, 360;FHI 360, SFH Nigeria, and PSI 2020b;USAID 2019;PSI et al 2019;Population Council 2016c;FHI 360 2012;Routes2Results et al 2019b;Danna et al 2019;FHI 360 2017;Van Der Straten et al 2010;Todd et al 2012;Bryant et al 2015;Gutin et al 2011;Ho and Wheeler 2018;Hubacher et al 2013;Da Costa et al 2019;Priyanka, Kaushik, and Paras 2015). For example, many studies found that women appreciated the long-acting nature of copper and hormonal IUDs because they saw this duration as convenient and low maintenance (Nanda et al 2018;Gottert et al 2015;Huber-Krum et al 2019;Mukamuyango et al 2020;Azmat et al 2012;Boller et al 2018;…”
Section: mentioning
confidence: 99%
“…An acceptable side effect profile was influential for the adoption of three methods: the diaphragm and copper and hormonal IUDs (Shapiro 2016;Harris and Angel 2020;Nanda et al 2018;Shapiro et al 2014;Huber-Krum et al 2019;Callahan et al 2019;Eva et al 2018;FHI360 and Family Health Options Kenya 2016;FHI 360, SFH Nigeria, and PSI 2020b;USAID 2019;PSI et al 2019;2019b;Danna et al 2019;FHI 360 2017;Bryant et al 2015;Hubacher et al 2013;Priyanka, Kaushik, and Paras 2015;Boller et al 2018;Marston et al 2016;A. Kumar et al 2018;Hayes and Kilbourne-Brook 2016b;Kyamwanga et al 2014;S.…”
Section: mentioning
confidence: 99%
See 3 more Smart Citations